Evaluation De Quatre Cultivars De Niebe (Vigna Unguiculata (L.) Walp.) Pour Leur Resistance Au Deficit Hydrique Et A L’adventice Parasite, Striga Gesnerioides (Willd.) Vatke Au Togo - Kondi, Yorikoume; Mawuli, Aziadekey; Agnassim, Banito; Yentchabre, Pocanam; Koffi, Tozo (European Scientific Journal, ESJ, 2018)
Drought and weed parasite Striga gesnerioides(Willd.)Vatke, are major constraints to cowpea production in sub-Saharan Africa. The purpose of this study was to examine the response of four cowpea (Vigna unguiculata(L.)Walp.)cultivars, VITOCO, VITA5, IT87D-10-10, and IT98K589-2 to water deficit, to a weed parasite S. gesnerioides and to determine the effect of this weed parasite on these cowpea cultivars under water deficit conditions. Pot experiment was conducted in a greenhouse condition under artificial infestation at the Agronomic Experimentation Station of Lomé. The experimental design was a split-split-plot design with three replications of two levels of S. gesnerioides;(presence and absence) in main plot, four water regimes; (periodic watering of 5, 10, 15 and 20 days) in sub-plot, and the cultivars in sub sub-plot. Data were collected on yield components (number of seed per pod, number of pod per plant and seeds weight per plant). Data collected on parasitic plantdate of emergence and its rate of emergence per pot. Water deficit tolerance was evaluated by the rank summation index (RSI).The results showed that the water régimes of 10 and 15 days had significant depressive effect on all yield components. The number of S. gesnerioides emerged per pot ranged from 10.20 (VITOCO) to 48.60 (IT98K589-2). In addition, the infestation of S. gesnerioides showed a significant reduction of all yield components evaluated in all tested cultivars. Therefore, no cultivar proved to be resistant, nor tolerant to S. gesnerioides.The overall rankings of the evaluated cultivars in terms of growth and yield parameters studied revealed that the cultivar IT98K-589-2 showed the best adaptive response in drought condition. The results also revealed that, the significant negative effect of water deficit on the seeds weight per plant is exacerbated by the S. gesnerioides infestation.